DEVELOPMENT OF INFORMATION SYSTEMS AND TECHNOLOGIES IN THE WORLD ECONOMY DURING COVID-19 - BELOZERTSEV, V.; KHARAKOZ, L.; KARMINOV, Y.; SOKOLOVA, O.; SYLYMA, H.; KHUDIAKOVA, H. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Nowadays humanity can’t live without information systems and technologies, which affect absolutely all areas of our daily life. They make a particularly significant contribution to the world economy. Information technologies allow to speed up the development of world trade on the Internet, provoke the emergence of the market of information and information services.In today's world, information technologies and systems are becoming more diverse and multifaceted. The spheres of their activity are changing and expanding, offering new qualities and characteristics of social development. The information component has been an important element for the formation of potential competition between countries and the development of international relations for decades.Technology affects the development of the economy, but there are many factors that affect the quality of technology and their modifications. One such factor is COVID-19 pandemic.  Pandemic has forced information technology to penetrate even deeper into human life. Now, with the help of IT, people not only are able to store, process, and analyze information, but also companies are capable of managing subordinates, and they in turn have the most comfortable conditions for work and achieving goals. And in general, due to pandemic systems for distance learning and delivery of any goods anywhere have been developed. After analyzing statistics, presented in this article, we can make a conclusion that over the past year, information technology has been greatly affected by the pandemic, but it has become an integral part of economic (and not only) development of countries. “Closed circle” has been created – due to the development of technology the state of the economy is improving, and together with the development of the economy more and more new technologies are needed.
Keywords: systems and technologies; analytics; COVID-19